Looking ahead: Future directions in, and future research into, second language acquisition - Larsen‐Freeman, Diane (Foreign language annals, 2018)
This article begins by situating modern‐day second language acquisition (SLA) research in a historical context, tracing its evolution from cognitive to social to sociocognitive accounts. Next, the influence of the zeitgeist is considered. In this era of rapid change and turmoil, there are both perils and opportunities afforded by globalization. In addition, what globalization is bringing to the forefront is a need to grapple with the complexity of the world. It follows then that we need to think differently about SLA. I suggest that this thinking take two directions. The first is that the researchers in the field adopt an ecological perspective, whereby the relations among factors are what is key to elucidating the complexity. I offer as an example overcoming the bifurcation between research on individual differences and research on the SLA process. Doing so ushers in a person‐centered, humanistic dimension of SLA. A second, related change is the renewed awareness of the importance of context and of the nature of constraints that shape any particular context. Language learning does not occur in an ideological vacuum but rather is affected in a serious way by prevailing beliefs in the society at large. I therefore make the case for language researchers to be more mindful of the social injustices that exist in the world concerning language learning and use, and I indicate several of the ideologies and myths that deserve to be challenged accordingly. Before concluding, I discuss the implications of these two changes for issues of language assessment, research, and teaching. Challenges How can the field of second language acquisition/development help learners to cope with the complexity and dynamism of the world we live in? An ecological approach that is considerate of the learning context and learners’ individual differences and that teaches them to adapt and make use of access‐creating affordances offers a logical choice.